Assessment of the Knowledge, Prevalence, and Control Strategies of Malaria Among Households in Sunyani Municipality, Bono Region, Ghana - Samuel Yaw Agyemang-Badu; Esi Awuah; Sampson Oduro-Kwarteng; Justice Yao Woelinam Dzamesi; Simon Agongo Azure (SAGE Publishing, 2023)
Background: Malaria remains a global public health concern for centuries. The study assessed the knowledge, prevalence and control strategies of malaria among households in the Sunyani Municipality, Bono Region, Ghana. Method: A simple random sampling method was used to administer semi-structured questionnaires to the respondents (n = 422). STATA version 14.0 was used to analyse the data and the results were presented in charts, graphs, and tables. Result: The study shows that the knowledge level of malaria, its vector of transmission and mosquitoes breeding sites among the respondents was quite high. Among the respondents, 43% reported to have been infected by malaria once in a year and 94% indicated that, their relatives have been infected with malaria parasites previously. Also, majority, 65% of the respondents selected environmental management and sanitation (EMS), followed by settlement (building houses) away from wetlands, 20.0% as alternative vector control methods to be employed to supplement the core vector control methods in the Municipality. Further, majority, 69% of the respondents indicated that enforcement of environmental sanitation bye-laws will compel residents to clean their environment, and this is likely to eliminate most mosquito breeding sites, whiles 46% called on Government to support, and employ more Environmental Health Officers and Sanitary Labourers, and adequately resource them to work effectively. Conclusion: Health authorities in the Sunyani Municipality must intensified education on malaria at all levels with the aim to influence the attitudes of households towards its prevention and control. Central and Local Government must employ more Environmental Health Officers, and empower and adequately resourced them to strictly enforce the environmental sanitation bye-laws. Malaria control authorities in the study area must consider employing environmental management and sanitation (EMS) and application of larvicides for mosquito larval control as alternative/supplementary malaria prevention and control methods to compliments the current core vector control methods.